2010
DOI: 10.1097/scs.0b013e3181c50fd6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Temporomandibular Joint Dislocation by Mandibular Distraction in a Patient With Melnick-Needles Syndrome

Abstract: Melnick-Needles syndrome is a congenital syndrome associated with severe architectural disorder of the skeletal system that can cause significant effects on the craniofacial skeleton including the mandible and temporomandibular joint. We report on a case of a young adult patient who experienced chronic dislocation, pain, and dysfunction of her temporomandibular joints related to both a severe bite dysfunction (mandibular hypoplasia) and the underlying bony architectural disorder associated with Melnick-Needles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
1
3
0
1
Order By: Relevance
“…Despite this reality and suboptimal vector of our elastics, we showed beneficial temporomandibular joint outcomes in our syndromic group of patients. Consistent with other reports, 19,20,35,36 the application of class II intermaxillary elastics alleviated strain and reduced incidence of postoperative pathology from 80 percent in the condylar-loaded compared with 7 percent in the condylar-unloaded patients (Fig. 7).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite this reality and suboptimal vector of our elastics, we showed beneficial temporomandibular joint outcomes in our syndromic group of patients. Consistent with other reports, 19,20,35,36 the application of class II intermaxillary elastics alleviated strain and reduced incidence of postoperative pathology from 80 percent in the condylar-loaded compared with 7 percent in the condylar-unloaded patients (Fig. 7).…”
Section: Discussionsupporting
confidence: 93%
“…18 Another report introduced a Melnick-Needles patient with chronic temporomandibular joint dislocation after bilateral distraction osteogenesis. 19 At our institution, it was noted that select patients with a syndromic diagnosis (Nager, Treacher Collins, Stickler, and other syndromes) developed functional problems, such as decreased mouth opening and poor oral intake following neonatal mandibular distraction. Based on these individual cases and anecdotal events from other reports, 18 -20 we set out to study differences between syndromic and nonsydromic patients with regard to (1) condylar anatomy and pathology and (2) outcomes related to the temporomandibular joint following neonatal mandibular distraction.…”
Section: Discussionmentioning
confidence: 98%
“…Aunque la correlación exacta entre la patología posoperatoria de la ATM y la edad del paciente sigue siendo debatida, alguna evidencia sugiere que el riesgo de anquilosis de la ATM y otras complicaciones aumenta con la edad. [12][13][14] La característica anatómica única de la vía respiratoria superior de los neonatos, a veces, dificulta la laringoscopía y la intubación. La presencia de anormalidades se suma a esta dificultad.…”
Section: Discussionunclassified
“…Several teams reported their surgical experience in such cases using various techniques. Kelley et al 11 reported the successful performance of bilateral mandibular distraction (with internal mandibular distraction device) to correct the malocclusion of a MNS patient. They added recombinant human bone morphogenetic protein 2 (rhBMP-2) during surgery to help bone healing as MNS is characterized by skeletal dysplasia.…”
Section: Discussionmentioning
confidence: 99%